Adherence to Mediterranean Diet of Breastfeeding Mothers and Fatty Acids Composition of Their Human Milk: Results From the Italian MEDIDIET Study - Di Maso, Matteo; Bravi, Francesca; Ferraroni, Monica; Agostoni, Carlo; Eussen, Simone R. B. M.; Decsi, Tamás; Quitadamo, Pasqua A.; Tonetto, Paola; Peila, Chiara; Profeti, Claudio; Salvatori, Guglielmo; Kazmierska, Iwona; et al. (Frontiers in Nutrition, 2022)
Background and Aims The content of fatty acids (FA) in human milk may be influenced by maternal nutrition. We evaluated the role of a Mediterranean diet in influencing the content of FA in human milk among 282 breastfeeding mothers participating in the MEDIDIET study. Materials and Methods Mediterranean Diet Score (MDS), a composite index, was used to evaluate adherence to the Mediterranean diet. It includes 9 components (i.e., vegetables, fruit, cereals, legumes, monounsaturated to saturated FA ratio – MUFA/SFA, fish, dairy products, meat, and alcohol) and therefore potentially ranges from 0 (no adherence) to 9 (complete adherence) points. None of the mothers obtained the highest score due to the low alcohol consumption in the study population. Mothers were categorized in approximate tertiles of adherence: 0–3 (34.4%), 4 (26.2%), and 5–8 points (39.4%). The mean content of FA across categories of MDS was compared using ANOVA and test for trend. Results A high adherence of breastfeeding mothers to the Mediterranean diet was associated with lower content of SFA in human milk (42.58 ± 4.36 for MDS = 0–3, 42.58 ± 4.89 for MDS = 4, and 40.92 ± 5.22% of fats for MDS = 5–8 points; p ANOVA and p for trend = 0.02). Conversely, a high adherence was associated with higher content of MUFA in human milk (43.27 ± 4.27 for MDS = 0–3, 43.27 ± 4.47 for MDS = 4, and 45.24 ± 5.22% of fats for MDS = 5–8 points; p ANOVA and p for trend < 0.01), ω-3 FA (1.07 ± 0.25 for MDS = 0–3, 1.22 ± 0.49 for MDS = 4, and 1.31 ± 0.51% of fats for MDS = 5–8 points; p ANOVA and p for trend < 0.01), and the major types of ω-3 FA (i.e., α-linolenic acid – ALA, eicosapentaenoic acid – EPA, docosahexaenoic acid – DHA, docosapentaenoic acid – DPA). These associations were mainly driven by the adherence to the vegetables, MUFA/SFA, fish, and dairy products components of the Mediterranean diet. Conclusion A high adherence to the Mediterranean diet was associated with human milk showing a lower content of SFA and higher content of MUFA and ω-3 FA, including DHA. The Mediterranean diet may contribute in human milk production with higher content of specific FA which is directly involved in infant’s neural and visual development, as reported by previous studies.